Role of American Policy in the Palestinian Catastrophe between 1939-1948: Prevention of Palestine Independence and Creation of the Jewish State - Rateb Al-Sweiti (My University, 2009)
This research investigates the American policy role in contributing to the Palestinian catastrophe by helping to create a Jewish state in Palestine in 1948. It defines the domestic American and international factors which affected the US policy on Palestine, and how it reflected on the American national interests in the Middle East. It discusses the American institutional participation in policy decision-making where the Zionists and their supporters played specific roles in defending the Jewish demands in Palestine. This work shows that they used their positions in the executive and legislative branches of government to create homogeneous American-Zionist interests to unify their activities in the US, foreign countries and the United Nations. It studies the development of the US-British cooperation with Zionism and its impact on the status of Palestine. These aspects of the research will also be analyzed by the use of historical methodology to find out the reasons responsible for the persistence of the US in taking a pro-Zionist stand in the face of Palestinian-Arab opposition. The findings of the research show that Zionism utilized the shared Western historical development and the common cultural basis to direct the American policy toward serving the Zionist interest in Palestine as an American interest, which put American and Arab interests in a lengthy conflict. The significance of this research lies within its emphasis on studying the American policy on Palestine during its most crucial period that witnessed the Palestinian catastrophe with establishing a foreign Zionist entity in 1948.

يستقصي هذا البحث دور السياسة الأمريكية في المساهمة بالمأساة الفلسطينية، وذلك في المساعدة بخلق دوله يهودية في فلسطين في عام 1948. ويحدد العناصر الأمريكية الداخلية والدولية التي تؤثر في اتجاه السياسة الأمريكية اتجاه فلسطين وكيف انعكست على المصالح الأمريكية في الشرق الأوسط. ويناقش هذا البحث مشاركة المؤسسات الأمريكية في صنع القرار السياسي الذي من خلاله لعب الصهاينة ومؤيدوهم أدوارًا محددةً في الدفاع عن المطالب اليهودية في فلسطين. ويبين هذا البحث أنهم استغلوا مراكزهم في السلطة التنفيذية والتشريعية للحكومة بخلق مصلحة أمريكية – صهيونية مشتركة لتوحيد نشاطاتهم في الولايات المتحدة، والدول الأجنبية والأمم المتحدة. ويدرس تطور التعاون الأمريكي - الإنجليزي مع الصهيونية وأثره على وضع فلسطين. استخدم البحث المنهجية التاريخية لكشف الأسباب المسئولة عن مواصلة الولايات المتحدة في اتخاذ موقف داعم للصهيونية في مواجهة المعارضة الفلسطينية – العربية. كشف البحث أن الصهيونية استخدمت التطور التاريخي الغربي المشترك والقاعدة الثقافية المشتركة لتوجه السياسة الأمريكية نحو خدمة المصلحة الصهيونية في فلسطين كمصلحة أمريكية الأمر الذي وضع المصالح الأمريكية والعربية في صراع طويل. تكمن أهمية هذا البحث بتركيزه على دراسة السياسة الأمريكية في فلسطين خلال أكثر حقبها خطورة والتي شهدت النكبة الفلسطينية بإقامة الكيان الصهيوني الغريب في 1948م.
دور السياسة الأمريكية في النكبة الفلسطينية بين عام 1939-1948: منع الاستقلال الفلسطيني وخلق دولة يهودية